Social exclusion, corruption, recall of authorities, inequality and fiscal centralization: inducers of social conflict in Peru (2016–2023) - Lauracio Ticona, Teófilo; Coyla Zela, Mario Aurelio; Ramos Rojas, Jarol Teófilo; Morales Rocha, José Luis; Serruto Medina, Genciana; Vargas Torres, Nakaday Irazema (Frontiers in Sociology, 2024)
The objective of the article was to investigate the possible inducing factors that contributed to determine the frequency of social conflicts at the subnational level in Peru between 2016 and 2021, including income inequality, social exclusion, fiscal centralism, corruption and revocation of authorities, for which four regression models were built. Disaggregated official data from the 24 departments and the provinces of Lima and Callao were analyzed. Economic inequality was associated with the Gini coefficient. To establish the association between social conflict and the inducers, it was estimated using Spearman’s Rho correlation coefficient. Statistical calculation was also employed to appreciate the collinearity between the inducers. The results showed that the revocation of subnational authorities determines 42.5% of social conflict. On the other hand, corruption and fiscal centralism determine 28.5% of the perception of suffering social exclusion. Inequality and social conflict determined 21.8% of the relevance of the execution and quality of public spending by the national government in the regions. Sixty percent of social conflicts in Peru are of an environmental nature. The population that has declared the greatest discrimination corresponds to Puno (28%). 55.6% of those surveyed consider corruption to be one of the country’s main problems. Corruption and social exclusion have a negative impact on the effectiveness of economic results and promote social conflicts. Inefficient use of fiscal resources translates into low quality of services and diminished credibility of the national and subnational governments. This situation highlights the need to design public policies that reduce conflicts and promote adequate governance.